Treatment of Subcorneal Pustular Dermatosis without Dapsone: A Case Report and Review of the Literature - Lindsey J. Wanberg; Brittney Schultz; Amrita Goyal (Hindawi Limited, 2024)
Subcorneal pustular dermatosis (SPD) is a rare neutrophilic dermatosis characterized by pustules on the trunk and intertriginous areas. While oral dapsone is the first-line treatment for SPD, alternative options are necessary for patients with glucose-6-phosphate dehydrogenase deficiency, drug hypersensitivity reactions, or refractory disease. To date, no consensus exists regarding next-best agents for SPD. In this report, we present a patient with significant SPD who developed dapsone hypersensitivity syndrome and then was successfully treated with colchicine and adalimumab. We propose that colchicine should be considered as a second-line treatment for SPD and present a therapeutic algorithm for clinicians to utilize when patients are not candidates for dapsone, have side effects requiring drug discontinuation, or have refractory disease.